Optimization of 4-Anilinoquinolines as Dengue Virus Inhibitors - Pei-Tzu Huang; Sirle Saul; Shirit Einav; Christopher R. M. Asquith (Molecules, 2021)
Emerging viral infections, including those caused by dengue virus (DENV) and Venezuelan Equine Encephalitis virus (VEEV), pose a significant global health challenge. Here, we report the preparation and screening of a series of 4-anilinoquinoline libraries targeting DENV and VEEV. This effort generated a series of lead compounds, each occupying a distinct chemical space, including 3-((6-bromoquinolin-4-yl)amino)phenol (12), 6-bromo-N-(5-fluoro-1H-indazol-6-yl)quinolin-4-amine (50) and 6-((6-bromoquinolin-4-yl)amino)isoindolin-1-one (52), with EC50 values of 0.63–0.69 µM for DENV infection. These compound libraries demonstrated very limited toxicity with CC50 values greater than 10 µM in almost all cases. Additionally, the lead compounds were screened for activity against VEEV and demonstrated activity in the low single-digit micromolar range, with 50 and 52 demonstrating EC50s of 2.3 µM and 3.6 µM, respectively. The promising results presented here highlight the potential to further refine this series in order to develop a clinical compound against DENV, VEEV, and potentially other emerging viral threats.